An ARDL Modelling Approach to Assess the Dynamic Effects of Economic Development and CO2 Emissions in Malaysia - Ding, Kee Zheng; Chan, Tze-Haw (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2024)
Abstract. This research paper conducts a comprehensive analysis of the complex relationship between CO2 emissions and economic factors, specifically investigating the Environmental Kuznets Curve (EKC) theory in Malaysia. Using data from 1991 to 2020, the study applies the Autoregressive Distributed Lag (ARDL) modelling approach developed by Pesaran et al. (2001). The results demonstrate a significant long-term connection between Gross Domestic Product (GDP), trade, and carbon emissions, indicating that economic development plays a crucial role in influencing Malaysia's carbon footprint. Additionally, the inclusion of institutional quality in the model adds another layer of complexity, highlighting the multifaceted nature of the relationship between economic progress and environmental outcomes. Furthermore, examining short-term dynamics using the ARDL model reveals diverse effects over time for variables such as renewable energy and institutional quality, providing a more nuanced understanding of these relationships. These detailed insights are essential for policymakers dealing with the challenges of promoting economic progress while ensuring environmental sustainability. The findings contribute to a deeper understanding of the interplay between economic variables and CO2 emissions, offering valuable guidance for policymakers striving to strike a balance between economic growth and environmental conservation in Malaysia. Keywords: Malaysia, autoregressive distributed lag (ardl) modelling, environmental kuznets curve (ekc), carbon dioxide (co2) emissions, gross domestic product (gdp), renewable energy (ren), institutional quality (iq), trade (tr)